SSR Markers Based Genetic Diversity in Nepalese Maize Landraces (SAARC Journal of Agriculture, 2020)
Knowledge on genetic diversity is necessary for developing new varieties and managing diversity for future use. Five SSR markers were used to develop the DNA finger prints and to assess the diversity of 23 Nepalese maize landraces. Five locus-based DNA finger prints have distinguished majority of the landraces. The average number of alleles was 2 per locus. Umc1333 marker had shown the highest gene diversity, heterozygosity and polymorphism information content (PIC). At landrace level, the highest gene diversity, heterozygosity and PIC values were found in Seto Local and Seti Makai-3. 23 maize landraces formed four clusters and these clusters were related with seed color. Name of landraces also reflected genetic similarity. Genetically similar landraces can be pooled for conservation and creating dynamic diversity rich population. Distantly related landraces (Bhirkaule, Local Seto Makai, Seto Makai-1, Makai Makai-1761) can be used in breeding program. Detection of low genetic diversity might be due to bottleneck effects during the collection of these landraces from farmers. Therefore, collection strategy needs to be revised for capturing maximum diversity.SAARC J. Agri., 18(1): 23-37 (2020)